Site-selective C–H functionalization to access the arene backbone of indoles and quinolines. (6th September 2021) - Prabagar, B.; Yang, Youqing; Shi, Zhuangzhi
Abstract : The site-selective C–H bond functionalization of heteroarenes can eventually provide chemists with great techniques for editing and building complex molecular scaffolds. Abstract : The site-selective C–H bond functionalization of heteroarenes can eventually provide chemists with great techniques for editing and building complex molecular scaffolds. During the past decade, benzo-fused N-heterocycles such as indoles and quinolines have been among the most widely investigated organic templates. Early developments have led to site-selective C–H bond functionalization on the pyrrole and pyridine cores of indoles and quinolines; however, C–H functionalization on the benzenoid ring has remained a great challenge in catalysis. In this review, we elaborate on recent developments in the highly challenging functionalization of C–H bonds on the less-reactive benzenoid core of indoles and quinolines. These findings are mainly described as selective directing group assisted strategies, remote C–H functionalization techniques and their reaction mechanisms. The underlying principle in each strategy is elucidated, which aims to facilitate the design of a more advanced structure of heterocycles based on bioactive molecules, synthetic drugs, and material aspects. Moreover, the challenges and perspectives for catalytic C–H functionalization to access the arene backbone of indoles and quinolines are also proposed in the conclusion section.